X+0.1x+1.7=(x-3.3)

Simple and best practice solution for X+0.1x+1.7=(x-3.3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+0.1x+1.7=(x-3.3) equation:


Simplifying
X + 0.1x + 1.7 = (x + -3.3)

Reorder the terms:
1.7 + X + 0.1x = (x + -3.3)

Reorder the terms:
1.7 + X + 0.1x = (-3.3 + x)

Remove parenthesis around (-3.3 + x)
1.7 + X + 0.1x = -3.3 + x

Solving
1.7 + X + 0.1x = -3.3 + x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-1.7' to each side of the equation.
1.7 + X + -1.7 + 0.1x = -3.3 + -1.7 + x

Reorder the terms:
1.7 + -1.7 + X + 0.1x = -3.3 + -1.7 + x

Combine like terms: 1.7 + -1.7 = 0.0
0.0 + X + 0.1x = -3.3 + -1.7 + x
X + 0.1x = -3.3 + -1.7 + x

Combine like terms: -3.3 + -1.7 = -5
X + 0.1x = -5 + x

Add '-0.1x' to each side of the equation.
X + 0.1x + -0.1x = -5 + x + -0.1x

Combine like terms: 0.1x + -0.1x = 0.0
X + 0.0 = -5 + x + -0.1x
X = -5 + x + -0.1x

Combine like terms: x + -0.1x = 0.9x
X = -5 + 0.9x

Simplifying
X = -5 + 0.9x

See similar equations:

| 7(v+8)=4v+1 | | 2x-9y=13 | | 2x-3=5x-17 | | X-1.1x-5.2=-5.5(x-2) | | -x/3+5=-10 | | (2/9)^2 | | (2/3)/(6/7) | | -(7y+8)=-7y-23 | | -13=x/8-3 | | 3+2y=4 | | -3w+6=2w-19 | | 1.1u-1.2=4.4u+5.4 | | 4/3+y=-4 | | 32-x=4(x+8) | | 6=c/-9 | | 6(-2)-2y=4 | | 6=c/-19 | | -5n-20=-4(4n+5) | | 96=-h-7h | | 6(13/6)-2y=4 | | 7=-4x+2-x | | 2u+8=-2(-u-4) | | 2(v+8)=v+19 | | 3(u+6)-5u=32 | | a-19=2 | | 12=-6k | | 3(28/13)-2y=6 | | 12z=0.8z | | 71=7x+8 | | 12a^3-24a^2= | | 3+(-2y)=6 | | 2x+5=-3x+15 |

Equations solver categories